GE_GERICHTE C/19112/2020 vom 17. Mai 2022 - GE Cour de justice (2022)
DIVORCE;OBLIGATION D'ENTRETIEN;CONJOINT;ENFANT;MAJORITÉ(ÂGE);REVENU HYPOTHÉTIQUE;LIQUIDATION DU RÉGIME MATRIMONIAL | CPC.157; CPC.164; CC.125; CC.204.al2; CC.207.al1; CC.276; CC.277.al2